2019
DOI: 10.4049/jimmunol.1900124
|View full text |Cite
|
Sign up to set email alerts
|

TNF-Producing Th1 Cells Are Selectively Expanded in Liver Infiltrates of Patients with Autoimmune Hepatitis

Abstract: Autoimmune hepatitis (AIH) is a chronic inflammatory liver disease that is believed to be driven by a CD4 + T cell response to liver Ags. However, the pathogenic function of CD4 + effector T cells in AIH is not fully understood. To characterize liver-infiltrating lymphocytes in AIH, we determined the cytokine production of infiltrating cells obtained from biopsy material by quantitative RT-PCR and flow cytometry. A cytokine quantitiative RT-PCR array of AIH specimens revealed that TNF was the most strongly upr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 43 publications
4
24
0
1
Order By: Relevance
“…The liver-infiltrating CD4 + T cells in Alb-iGP_Smarta mice were dominated by Th1 cells producing IFN-γ (37.5%, Figure 3E; P = 0.0012), which were significantly increased as compared with Alb-iGP control mice (8.6%). Interestingly, and in accordance with our recent findings in human AIH (36), the liver-infiltrating Th1 cells in Alb-iGP_Smarta mice were marked by coproduction of IFN-γ and TNF in liver (Figure 3F and Supplemental Figure 2B; P = 0.0012), indicating potent inflammatory activation. The fraction of IL-17 producers among the intrahepatic CD4 + T cells was also elevated in Alb-iGP_Smarta mice (14.8 vs. 2.2% in Alb-iGP controls; Figure 3G; P = 0.0003).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The liver-infiltrating CD4 + T cells in Alb-iGP_Smarta mice were dominated by Th1 cells producing IFN-γ (37.5%, Figure 3E; P = 0.0012), which were significantly increased as compared with Alb-iGP control mice (8.6%). Interestingly, and in accordance with our recent findings in human AIH (36), the liver-infiltrating Th1 cells in Alb-iGP_Smarta mice were marked by coproduction of IFN-γ and TNF in liver (Figure 3F and Supplemental Figure 2B; P = 0.0012), indicating potent inflammatory activation. The fraction of IL-17 producers among the intrahepatic CD4 + T cells was also elevated in Alb-iGP_Smarta mice (14.8 vs. 2.2% in Alb-iGP controls; Figure 3G; P = 0.0003).…”
Section: Resultssupporting
confidence: 91%
“…Accordingly, the pathogenic activation of GP-reactive CD4 + T cells in mice was marked by coproduction of the classical Th1 cytokines IFN-γ and TNF (Figure 3F). Of note, we found a similar dominance of IFN-γ and TNF coproducers among the liver-infiltrating CD4 + T cells in human AIH (36), indicating that this cytokine signature might be relevant for AIH pathogenesis. Our findings reemphasize the previously reported pathogenic role of IL-12 in murine AIH (19).…”
Section: What Drives the Activation Of Autoreactive Effector T Cells?supporting
confidence: 56%
“…Furthermore, the presence of T H 17 cells and T cells coproducing IFN-γ and TNF-α was reported in AIH [12,103]: Findings indicated that TNF-α-producing CD4 + T cells were significantly expanded, both in blood and liver of AIH patients. However, the majority of the TNF-α-producing CD4 + T cells in AIH also co-produced IFN-γ, suggesting that these cells might represent a pathogenic activation state of T H 1 cells [12].…”
Section: T H 1 Cellsmentioning
confidence: 94%
“…IFN-γ plays a crucial role in generating efficient innate and adaptive immune responses [134] . Studies have found an association of Th1 cells with organ-specific autoimmune diseases such as autoimmune type 1 diabetes [135] , rheumatoid arthritis [136] , multiple sclerosis [137] , and Crohn's disease [138] . In terms of liver diseases, Th1 cells are associated with AIH [139] , PBC [140] , and alcohol-related cirrhosis [141] .…”
Section: Basic Characteristics Of Th1 Cellsmentioning
confidence: 99%